Sexualidade e deficiência mental: impacto de um programa de orientação para famílias. - Amaral, Mariana Clivati do (2004)
Considering the relevance of the family in the process of sexual education and for the promotion of the development of mental disabled people, the objective of this study was to identify possible variable that can have influenced the changes in the conceptual repertoires and of behaviors of eight parents of mental disabled teenagers and adults, through of a Program of Sexual Orientation that included information about concepts and behaviors in relation to the sexuality of mental disabled people. The Program of Sexual Orientation was developed by means of activities and quarrels guided for considered aspects excellent constituted of conditions to facilitate the doubts and anxiety manifestations from the participants, inclusion of social determinants in the analysis of the situation involving sexuality, conditions to facilitated the identification of values and behaviors presents and important in situations that involve sexuality, presentation of practices and concretes situations involving sexuality for examination by the participants and conditions to facilitate de examination of the influence of parents values and behaviors over theirs disabled suns behaviors. Two independents groups were arranged, each one with parents of users from a different institution, both with equal number of participants. The data for characterization and verification of eventual changes in the repertoires of the participants were obtained by means of structuralized interviews individual. Introduced for one group in a week and for the other in two weeks later, the program was applied in five sessions with each group. The design used was before and after for each group. All the changes observed in the accounts of the participants of the two groups, from the exposition to the program, they had been of unfavorable for favorable in terms of sexual development of mental disabled people, in relation the aspects as: a) capacity of the mental disable suns and daughters of having sexual wishes, to understand sexual issues, to control their sexual manifestations and to construct affective relationships; b) incentive the social contacts amplification and social integrate; c) compatibility of the treatment given to family members which presents mental deficiency considering their age and emotional maturity, incentive the autonomy and independence; d) compromising of the family in the sexual education and offer reports about sexuality and constraint to deal with sexual issues; e) acceptance or repression to sexual manifestation and recognition of their suns and daughters mental disabled rights of exercise the sexuality. The changes had varied in degree and distribution of a group for another one and inside of the same group, for different people. Age of the daughters, initial repertoire and characteristics of the institution are some possible variables that can be related to these differences among participants and between groups.